Implementation of IoT-based Appropriate Technology in the Rabbit Farming Group in Sumberejo Village - Dura, Justita; Hadi, Abd; Sidi, Agus Purnomo (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service activity aims to improve the productivity and welfare of rabbit breeders through the implementation of innovative Internet of Things (IoT)-based cages. This innovation includes automatic monitoring of cage temperature and humidity and an automated roll system for waste disposal. Method: The program is implemented using extension, training, practice, and equipment handover methods at the "Ternak Kelinci" Livestock Group, Sumberejo Village, Batu City. Practical Applications: IoT devices enable real-time monitoring of cage conditions via smartphone, while automated roll systems help maintain cage cleanliness and reduce the risk of disease. Conclusion: This program has succeeded in increasing farmers' knowledge about modern cage management, making livestock care easier, and is expected to reduce rabbit mortality rates and increase farmers' income.